A case of acute intoxication due to combined use of fentanyl and 3, 4-dichloro-N-[2-(dimethylamino)cyclohexyl]-N-methylbenzamide (U-47700). (September 2016) - Coopman, Vera; Blanckaert, Peter; Van Parys, Geert; Van Calenbergh, Serge; Cordonnier, Jan
Highlights: Fatality involving fentanyl and U-47700: case histories and analytical findings. Determination of U-47700 in blood and urine by UPLC–MS/MS: method validation. The recognition and analysis of highly potent NPS in tissues are challenging. Synthetic opioid used as a 'legal' substitute of morphine and heroin. The case illustrated the dangers associated with new synthetic opioids. Abstract: A 30-year old man was found dead in his home after inhaling fumes of a powder burned on aluminum foil. Blood and urine were taken by the medical examiner during the external body examination and submitted to the laboratory for a comprehensive systematic toxicological analysis. A toxic fentanyl level of 10.9 μg/L was measured in the subclavian blood. Police investigation revealed that the man searched the internet for information on new psychotropic substances, among others including U-47700. A powder found in the victims' home was transferred to the laboratory for analysis, in which trace amounts of fentanyl (0.0035%, m/m) and U-47700 (0.0012%, m/m) were identified by gas chromatography mass spectrometry. U-47700 is an opioid analgesic drug, considered to have a potency of approximately 7.5 times that of morphine. A target analysis on U-47700 was performed using liquid–liquid extraction and ultra performance liquid chromatography tandem mass spectrometry operating in multiple reaction monitoring mode. The method validation was based on the Scientific Working Group of Forensic Toxicology document 'Standard Practices of Method Validation in Forensic Toxicology'. In blood and urine the U-47700 concentration was 13.8 and 71.0 μg/L, respectively. To the author's knowledge, this is the first case report of a fatal intoxication involving U-47700 abused as a new psychotropic substance.